USING QUARTET CARD AS MEDIA TO IMPROVE THE RECOUNT TEXT WRITING SKILL OF THE ELEMENTARY LEVEL STUDENTS OF INTENSIVE ENGLISH COURSE (IEC) MAGELANG IN THE SCHOOL YEAR 2017/2018 - Kamalia Mardini (Faculty of Education and Teachers Training, 2018)
The goal of the English teaching and learning for senior high school students in Intensive English Course (IEC) is to be able to develop the four language skills, one of them is writing. The students’ achievement in writing recount text on the Elementary level of IEC is less than the standard minimum score of the learning target. This condition is caused by the students’ low motivation and the monotonous teaching media used by the teacher.To solve these problems, the researcher attempts to use Quartet Cards in teaching writing recount text. The objectives are to know whether the use of Quartet Cards can improve the students’ motivation in learning the recount text writing skill.This research belongs to Classroom Action Research and the subject of this research is the students of Elementary Level of Intensive English Course Magelang. The researcher implements Pre-Cycle, Cycle I and Cycle II. Each cycle consists of planning, acting, observing and reflecting. To collect the data, the researcher used non-test (observation, questionnaires and documentation) and test. The data was analyzed using qualitative and quantitative data analysis.Based on the researcher’s observation and questionnaire, it showed that there was an increase of the students’ learning motivation in writing recount text after the researcher taught using Quartet Cards. In addition, the improvement also occurred in writing test. In Pre-Cycle the mean score was 68.35, it became 74.85 in Cycle I and 81.40 in Cycle II. The total improvement from Pre-Cycle to Cycle II test was 13.05 points IN THE SCHOOL YEAR 2017/2018